The study on the adsorption characteristics of anthracite under different temperature and pressure conditions - Danan Zhao; Xiaofei Ke; Mincong Huang; Wenchang He; Mingyu Tong; Baihong Chen; Qu Du (PLoS ONE, 2025)
The study of the adsorption characteristics of coal is of great significance to gas prevention and CO2 geological storage. To explore the adsorption mechanism of coal, this study focuses on columnar anthracite. Adsorption tests on coal rock under a range of physical field conditions were conducted using the volumetric method. The adsorption characteristics of anthracite for CO2, CH4, and N2 gases under different conditions were investigated using Grand Canonical Monte Carlo (GCMC) and Molecular Dynamics (MD) methods. The results showed that the adsorption capacities of anthracite for these three gases are in the order of CO2 > CH4 > N2, and that the adsorption capacity increases with increasing gas injection pressure. The CO2/CH4/N2 gas molecule adsorption capacity of the anthracite macromolecular structure model decreases with increasing temperature. The increase in temperature has the greatest influence on the CO2 absorption capacity, followed by the CH4 and N2 adsorption capacities. The research offers a theoretical basis for the control of coal mine gas and the geological storage of CO2.